Anya Forger’s Childhood Trauma in Spy X Family Season 1 (2022): Cathy Caruth’s Trauma Theory - Dyah Ningrum Jaya Wisnu Murti - (LITERA KULTURA : Journal of Literary and Cultural Studies, 2026)
This study analyzes the representation of childhood trauma in Spy × Family Season 1 (2022) using Cathy Caruth’s trauma theory. Although the anime is widely recognized as a family comedy, it implicitly portrays traumatic experiences through the characterization of its child protagonist, Anya Forger. This research focuses on examining how childhood trauma is represented through narrative structure, characterization, and visual symbolism, as well as how Anya’s traumatic experiences reflect Caruth’s concept of trauma as an unassimilated experience that returns through repetition and delayed understanding (belatedness).